Smart Food Bank Application : Towards Zero Hunger for UUM Community - ChePa, Noraziah; Earn, Tan Jia; Abu Bakar, Nur Azzah; Md. Zain, Rajwani; Sie-Yi, Laura Lim (Multidisciplinary Applied Research and Innovation, 2022)
Universiti Utara Malaysia (UUM) is the fourth university to launch a food bank for its students and the launching ceremony was officiated by His Majesty the Sultan of Kedah. Since its launched in September 2019, it is operated manually. Due to overwhelming donations from many parties, there are some issues faced in managing the food bank efficiently, particularly in reaching out to students who are really in need. With the aim of having an efficient management of food bank towards achieving zero hunger among UUM community, a smart food bank application is designed and developed in mobile environment and running on Android platform. The application can be utilized by three main users; admin at the Division of Students Support and services (SSSD), under The Student Affairs Department (HEP), applicants (among less fortunate B40 students and admin staff of student’s hostel, and potential donors. The main functions are the management of food stock, food allocation, application of food, donations, as well as managing the registered users. Applicants can utilize the application by requesting for food (share their location on UUM map) and view their application status. Potential donors can offer their donation by sharing their location to be picked up by the admin. All functions are designed in facilitating these three main parties towards better management of UUM food bank. The project is aligned with the second and third goal of Sustainable Development Goals (SDG) which focusing on zero hunger and good health and well-being, respectively. It can serve as a platform in providing good food to UUM community to achieve the targeted SDG goals. It is believed that this smart food bank application can also serve as a platform in planning a suitable food allocation program in serving the less fortunate group of UUM community and perhaps at some points may improve the quality of life of the students. Due to its positive findings, feedbacks, and impacts, smart food bank application can be further applied to other food bank facilities or similar bodies offering the same services towards achieving zero hunger in a bigger context.